Gender Analysis of Ornamental Fish Production Units in Maharashtra, India - Yadav, Bharat; Sharma, Arpita (Frontiers in Marine Science, 2022)
Ornamental fisheries is an emerging business and has vast opportunity. In India, Maharashtra state had a scheme called as “Rainbow Revolution” which was started to encourage breeding and export of ornamental fishes. Taking advantage of this scheme 305 men and women entrepreneurs took up this small scale business. Gender analysis which provides necessary data and information to integrate a gender perspective into policies, programmes and projects and allows for development of interventions that address gender inequalities was conducted using Harvard Analysis Framework for men and women entrepreneurs involved in ornamental fish production. The objectives were to explore factors which influenced entrepreneurs to take up this business and to map activity, access and control profile of men and women entrepreneurs involved in ornamental fish production. Out of 305 ornamental production units under rainbow revolution scheme, 110 units were studied out of which 82 were owned by men and 28 by women. Influencing factors to take up this business by both men and women were community norms, prevailing social hierarchy, demographic factors and access to special training. Activity profile revealed that men were involved in construction of ornamental fish production unit, observation and checking fish health, checking water parameters, live food culture, marketing, upkeep and maintenance and it was found that they spent average of 8 hours/day in this. Women’s involvement was in fish feeding, cleaning of tanks, siphoning, feed preparation and marketing for average 4 hours/day. Many activities like feeding, cleaning of tanks and siphoning, feed preparation, setting of fish for breeding, removal of offspring and marketing were performed by both. Men had higher access and control on resources like land, farm, machine, equipment and finances. Mann-Whitney U test revealed statistically significant difference between men and women’s access and control on resources. Study has revealed that in addition to family and house responsibilities, women spend 4 hours/day on this business. They have less access and control on resources because of existing power relations with which we conclude that men and women cannot be treated as homogeneous categories when designing any schemes/policy interventions.